2010
DOI: 10.1002/ceat.201000237
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Iterative Scheme for Design of Experiments in Complex Polymerizations

Abstract: The Bayesian design approach is an experimental design technique which has many advantages over standard experimental designs. It incorporates prior knowledge about the process into the design to suggest a set of future experiments in an optimal, sequential, and iterative fashion. Since for many complex polymerizations prior information is available, either in the form of experimental data or mathematical models, the use of Bayesian design methodology could be beneficial. Exploiting this technique in complex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Even more recently, Nabifar et al, [2] in a companion paper, expanded on and reinforced the advantages of the Bayesian technique by looking at additional polymerization case studies and demonstrating the attractiveness of the technique, which can suggest a set of future process experiments in an optimal, sequential and iterative fashion. Exploiting the Bayesian design in complex polymerizations (and in other processes, since the technique is perfectly general), could hopefully lead to optimal performance in fewer trials, thus saving time and money.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Even more recently, Nabifar et al, [2] in a companion paper, expanded on and reinforced the advantages of the Bayesian technique by looking at additional polymerization case studies and demonstrating the attractiveness of the technique, which can suggest a set of future process experiments in an optimal, sequential and iterative fashion. Exploiting the Bayesian design in complex polymerizations (and in other processes, since the technique is perfectly general), could hopefully lead to optimal performance in fewer trials, thus saving time and money.…”
Section: Introductionmentioning
confidence: 92%
“…Two typical questions that often arise in Bayesian design implementations have to do with how effectively one can make statements about the quality of prior knowledge and the significance of the estimated effects (from the designed experiments), and about the gain in information content. These two important questions were not addressed in detail in earlier Bayesian design implementations, [1][2][3][4] and hence they are the topic of the present contribution. In other words, the following questions, intimately related to the Bayesian experimental design technique, will be addressed in what follows: (1) What statistical diagnostic criteria can one use in order to shed light on the quality of prior knowledge (see step 3, and implicitly step 2, of Table 3) and the significance of estimated effects (see step 7 of (1) and (2) above not only clarifies the design steps further but also could only make one more confident in the effectiveness and practicality of the Bayesian design of experiments procedure.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is the goal of sequential Bayesian design of experiments. These techniques have been used in polymerization and in many general Chemical Engineering modeling studies before, for the purpose of both modeling/parameter estimation and model discrimination …”
Section: Introductionmentioning
confidence: 99%
“…This technique uses process models to design experiments in an optimal way in order to maximize the information that can be extracted from them and minimize the experimental effort required to estimate model parameters. Nabifar et al [129] demonstrated the benefits of the Bayesian design methodology in complex polymerization processes using an NMP system as a case study. Scott et al [130] carried out a model-based D-optimal design of experiments in the NMP of styrene.…”
mentioning
confidence: 99%